Biodegradation and toxicity of emerging contaminants: Isolation of an exopolysaccharide-producing Sphingomonas sp. for ionic liquids bioremediation - Koutinas, Michalis; Vasquez Christodoulou, Marlen; Nicolaou, Euthimia; Pashali, Petros; Kyriakou, Eleni; Loizou, Elena; Papadaki, Aikaterini; Koutinas, Apostolis A.; Vyrides, Ioannis (My University, 2019)
Ionic liquids (ILs) have been characterized as contaminants of emerging concern (CEC) that often resist biodegradation and impose toxicity upon environmental release. Sphingomonas sp. MKIV has been isolated as an extreme microorganism capable for biodegradation of major classes of ILs. Six imidazolium-, pyridinium- and ammonium-based ILs (pyridinium trifluoromethanesulfonate [Py][CF3SO3], 1-(4-pyridyl)pyridinium chloride [1-4PPy][Cl], 1-butyl-3-methylimidazolium bromide [BMIM][Br], 1-butyl-3-methylimidazolium methanesulfonate [BMIM][MeSO4], tetrabutylammonium iodide [n-Bu4N][I] and tetrabutylammonium hexafluorophosphate [n-Bu4N][PF6]) were used for microbial growth. The strain achieved 91% and 87% removal efficiency for cultures supplemented with 100 mg L-1 of [BMIM][MeSO4] and [n-Bu4N][I] respectively. The metabolic activity of MKIV was inhibited following preliminary stages of cultures conducted using [BMIM][MeSO4], [BMIM][Br], [Py][CF3SO3] and [n-Bu4N][PF6], indicating potential accumulation of inhibitory metabolites. Thus, a comprehensive toxicological study of the six ILs on Aliivibrio fischeri, Daphnia magna and Raphidocelis subcapitata was conducted demonstrating that the compounds impose moderate and low toxicity. The end-products from [BMIM][MeSO4] and [n-Bu4N][I] biodegradation were assessed using Aliivibrio fischeri, exhibiting increased environmental impact of the latter following biotreatment. MKIV produced 19.29 g L-1 of biopolymer, comprising mainly glucose and galacturonic acid, from 25 g L-1 of glucose indicating high industrial significance for bioremediation and exopolysaccharide production.
Keywords: Ionic liquid; Biodegradation; Toxicity assessment; Extracellular polymeric substances; Emerging contaminants